METHOD OF QUALITATIVE ASSESSMENT OF THE HUMAN INTELLECTUAL POTENTIAL AT A DIGITAL ENTERPRISE - Loseva, Olga; Abdikeev, Niyaz; Melnichuk, Marina (Revista Inclusiones, 2020)
The issue of building effective teams capable to create, implement and commercialize innovative products is highly relevant for high-tech companies focused on business digitalization. The article suggests a solution based on the methodology for assessing human intellectual potential. The sensory, emotional, logical, creative, socio-cultural and economic components of intelligence are detailed and their functional interaction in the implementation of innovative team activities is described. The methods for determining the integral indicator of individual intellectual potential based on a weighted score of the structural components of intelligence are presented. The algorithm for finding the synergy coefficient as well as the human intellectual potential of the team is described. Some new areas for application of the developed methodology are suggested based on the results of testing.